SiC/GaN power semiconductor devices: a theoretical comparison and experimental evaluation under different switching conditions - Li, Ke; Evans, Paul; Johnson, Mark (Institution of Engineering and Technology, 2017)
The conduction and switching losses of SiC and GaN power transistors are compared in this paper. Voltage rating of commercial GaN power transistors is less than 650V while that of SiC power transistors is less than 1200V. The paper begins with a theoretical analysis that examines how the characteristics of a 1200V SiC-MOSFET change if device design is re-optimised for 600V blocking voltage. Afterwards, a range of commercial devices (1200V SiC-JFET, 1200V SiC-MOSFET, 650V SiC-MOSFET and 650V GaN-HEMT) with the same current rating are characterised experimentally and their conduction losses, inter-electrode capacitances and switching energy Esw are compared, where it is shown that GaN-HEMT has smaller ON-state resistance, inter-electrode capacitance values and Esw than SiC devices. Finally, in order to reduce device Esw, a zero voltage switching circuit is used to evaluate all the devices, where device only produces turn-OFF switching losses and it is shown that GaN-HEMT has less switching losses than SiC device in this soft switching mode. It is also shown in the paper that 1200V SiC-MOSFET has smaller conduction and switching losses than 650V SiC-MOSFET.